2019
DOI: 10.17305/bjbms.2018.3195
|View full text |Cite
|
Sign up to set email alerts
|

A plea for an extension of the anatomical nomenclature: Organ systems

Abstract: This article is the third part of a series aimed at correcting and extending the anatomical nomenclature. Communication in clinical medicine as well as in medical education is extensively composed of anatomical, histological, and embryological terms. Thus, to avoid any confusion, it is essential to have a concise, exact, perfect and correct anatomical nomenclature. The Terminologia Anatomica (TA) was published 20 years ago and during this period several revisions have been made. Nevertheless, some important an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Based on the above-stated definitions, hypotheses, and facts, it is necessary to continue research concerning the prevalence and classification of anatomical variants and refine the associated nomenclature. Without unanimous and simple variant nomenclature, communication among anatomists, clinicians, students, and teachers will continue to be confused [ 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ].…”
Section: Anomalies and Terminologymentioning
confidence: 99%
“…Based on the above-stated definitions, hypotheses, and facts, it is necessary to continue research concerning the prevalence and classification of anatomical variants and refine the associated nomenclature. Without unanimous and simple variant nomenclature, communication among anatomists, clinicians, students, and teachers will continue to be confused [ 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ].…”
Section: Anomalies and Terminologymentioning
confidence: 99%
“…The newly proposed terms, either by the Consensus documents or by other authors during research in last 10 years (if found relevant), are written in bold italics. [8][9][10][17][18][19][20][21][22][23]…”
Section: Introductionmentioning
confidence: 99%
“…Their terminology should match the nervous counterparts, i.e. plexus vasculosus myentericus located between the stratum longitudinale and stratum circulare tunicae muscularis and plexus vasculosus submucosus located with the submucosa [ 3 , 51 ]. Rami retroperitoneales anteriores* are direct fine branches from the aorta abdominalis , the arteria renalis and the arteria renalis accessoria , the arteria testicularis or the arteria ovarica , and the arteria iliaca communis .…”
Section: Arteriaementioning
confidence: 99%
“…We have also repetitively stressed the importance of anatomical nomenclature in enabling clear, unanimous and unambiguous communication among specialists. All revised or newly proposed terms to be potentially incorporated into the only official valid version of the anatomical nomenclature called Terminologia Anatomica (TA) are summarized in these articles [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation